PENERAPAN PROGRAM KESELAMATAN DAN KESEHATAN KERJA DI LABORATORIUM UJI TANAH PADA PT. X - Indriani, Levina Putri; Warmana, G. Oka (Gapenas Publisher, 2025)
The most important aspect in creating a safe and healthy work environment is occupational safety and health, especially in laboratory areas that are at risk of accidents. The purpose of this study is to understand and analyze the implementation of occupational safety and health programs for PT X employees. This study uses a descriptive research methodology that is adapted to the research objectives. The method used in this study is a quantitative approach with a minimum sample of 14 respondents. The research findings indicate that PT X's human resource management has succeeded in developing employees, especially in OHS knowledge and work-related tasks. PT X has never experienced work-related incidents in the laboratory, which indicates that human health is generally going well.